EALLU; Indigenous Youth, Arctic Change & Food Culture - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group, 2017)
Over millennia, Arctic Indigenous People' culinary traditions and food culture have nourished peoples, enriched communities, bound generations and embodied the very essence of 'sustainability'. Indigenous food production and processing systems ensured that by connecting to the deep cycles of the seasons, sun and moon, and their specific ecological niches, and their rich knowledge, herders, hunters, fishers and gatherers could sustain human and animal life over thousands of years. This is not 'Traditional Knowledge' constructed in the form of a declaration or political statement. This is ancient knowledge enacted in the everyday. This is a book about the fabulous abundance and diversity of food in the Arctic. While many think of the Arctic as a place of harsh climate and scarcity, in fact the Arctic hosts an extraordinary food culture, built on 10,000 years of knowledge, and intergenerational knowledge transfer. The Eallu cookbook won the prize for Best Cookbook at the 2018 Gourmand awards.